The International Physical Activity Questionnaire-long form overestimates self-reported physical activity of Brazilian adults - Sebastiao, E.; Gobbi, S. [UNESP]; Chodzko-Zajko, W.; Schwingel, A.; Papini, C. B. [UNESP]; Nakamura, P. M. [UNESP]; Netto, A. V. [UNESP]; Kokubun, Eduardo [UNESP] (W B Saunders Co Ltd, 2012)
Objective: To explore issues associated with measuring physical activity using the International Physical Activity Questionnaire (IPAQ)-long form in adults living in a mid-sized Brazilian city.Methods: A stratified random sampling procedure was used to select a representative sample of adults living in Rio Claro. This yielded 1572 participants who were interviewed using the IPAQ-long form. The data were analysed using standard statistical procedures.Results: Overall, 83% of men and 89% of women reported at least 150 min of combined moderate and/or vigorous physical activity per week. Reliable values of leisure and transportation-related physical activity were observed for both males and females. With regard to the household and work-related physical activity domains, both males and females reported unusually high levels of participation.Conclusion: The IPAQ-long form appears to overestimate levels of physical activity for both males and females, suggesting that the instrument has problems in measuring levels of physical activity in Brazilian adults. Accordingly, caution is warranted before using IPAQ data to support public policy decisions related to physical activity. (C) 2012 The Royal Society for Public Health. Published by Elsevier Ltd. All rights reserved.
Keywords: Adults; Assessment; Survey design; IPAQ; Questionnaires